Dynamics of structures: theory and applications to earthquake engineering - Chopra, Anil K (Pearson Education, 2003)
Dynamics of structures: theory and applications to earthquake engineering / Chopra, Anil K. -- Delhi: Pearson Education, 2003 624.1762 C549e2 2nd ed. No. of Copies : 1